A Case Study on the Management of Psoriasis (Kitibha) by Ayurvedic Intervention (International Journal of Ayurveda and Pharma Research, 2022)
Psoriasis (Kitibha) is one of the most common chronic skin disorders, which has psychological and social impact on patient’s life. This disease is not contagious and may affect people of any age, but it commonly begins around 15 to 40 years. Psoriasis is commonly red and white hues of scaly patches appearing on the top of skin. This disease is equated to Kitibha in Ayurveda due to its invariable similarities in signs and symptoms. This case study aims to investigate whether Ayurvedic intervention can manage moderate to severe Psoriasis (Kitibha). A 41‑year old male came to the Outpatient Department (OPD) of Central Ayurveda Research Institute, Guwahati with clinical features indicative of Psoriasis. This case was diagnosed as Kitibha and was managed by Ayurvedic interventions of Kaishore Guggulu 1gm twice a day, Arogyavardhini vati 500mg twice a day, Panchtiktaguggulu Ghrit 3 gm twice a day and Brihat Marichyadi tail local application twice a day for 3 months at OPD level. The response to the treatment was found to be highly effective. At the end of the treatment period and follow up of 1 month as compared with baseline, highly significant changes were observed. Kaishore Guggulu, Arogyavardhini vati, Panchtiktaguggulu Ghrit and Brihat marichyadi tail in the above‑mentioned doses were found to be very effective and safe in moderate to severe case of Psoriasis (Kitibha).